Implementation Of Social Media Promotion Strategy And Product Innovation In Business Development Case Study At CV Iyog Sport - Evi Fitrotun Najiah; Henny Mahmudah; Maharani Adinda F.P (Sean Institute, 2025)
The rapid advancement of digital technology has driven many companies to utilize social media as an effective promotional tool. CV Iyog Sport, a jersey printing convection company, also leverages social media platforms such as Instagram, Shopee, TikTok Shop, and YouTube to support their business development. This business has been well received by the Indonesian community and is widely recognized as a high-quality, modern, and leading garment company in service. This study aims to analyze the implementation of promotional strategies through social media and product innovation in the business development of CV Iyog Sport. The research method used is an in-depth case study, which includes the collection of primary and secondary data through interviews, observations, and analysis of company documents. The results of the research show that the implementation of promotional strategies using social media has successfully increased the visibility and sales of CV Iyog Sport's products. The product innovation efforts also received positive responses from consumers, which in turn fosters business growth. Overall, this study concludes that a combination of appropriate social media promotional strategies and product innovation can significantly contribute to the business development of CV Iyog Sport.